2019
DOI: 10.19044/esj.2019.v15n7p177
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Assessment Tools for the Writing Skill Development of EFL Learners

Abstract: This paper focuses on improving the writing skill through the application of strategies based on alternative assessment to EFL students in a private university of Ecuador. This inquiry analyses how the application of alternative assessment tools affect the development of the writing skill of EFL learners. The target population of this study was 23 students who take English lessons at the first level. This research used the quasi-experimental design with an experimental group only. The instruments used to colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Writing skill was one of the most focused skills in the reviewed studies. A total of 7 studies (Yurdabakan and Erdogan, 2009;Kalra, Sundrarajun and Komintaracat, 2017;Cuesta, Mayorga, Padilla and Mayorga, 2019;Iraji, Enayat and Momeni, 2016;Moradan and Hedayati, 2012;Javaherbakhsh, 2010) reported the positive influence of alternative assessment strategies on students' writing skills ranging from simple writing to argumentative writing skill. Based on the findings of the reviewed studies, portfolio and self-assessment were found the most used strategies to enhance writing skill among other strategies such as peer-assessment, conferencing, etc.…”
Section: Methods Of Alternative Assessment and Their Effects On Language Skillsmentioning
confidence: 99%
“…Writing skill was one of the most focused skills in the reviewed studies. A total of 7 studies (Yurdabakan and Erdogan, 2009;Kalra, Sundrarajun and Komintaracat, 2017;Cuesta, Mayorga, Padilla and Mayorga, 2019;Iraji, Enayat and Momeni, 2016;Moradan and Hedayati, 2012;Javaherbakhsh, 2010) reported the positive influence of alternative assessment strategies on students' writing skills ranging from simple writing to argumentative writing skill. Based on the findings of the reviewed studies, portfolio and self-assessment were found the most used strategies to enhance writing skill among other strategies such as peer-assessment, conferencing, etc.…”
Section: Methods Of Alternative Assessment and Their Effects On Language Skillsmentioning
confidence: 99%
“…ZipGrade is a mobile application that uses a device's camera to scan and grade multiple-choice answer sheets. For lecturers who give paper-based multiple-choice tests or researchers who want to collect multiple-choice responses on paper [1]. The time-saving benefits of marking and collecting data by simply using a smartphone camera to scan an answer sheet are enormous [2].…”
Section: Introductionmentioning
confidence: 99%